Long-pot-life color-stable epoxide composition
By using a composition of non-aromatic epoxy resin, anhydride curing agent and nitrogen-containing catalyst, the color instability of epoxy materials under heat, ultraviolet light and chemicals is solved, achieving long-term storage stability and color stability, making it suitable for adhesives and coatings for electronic devices.
Patent Information
- Application Number
- CN202380042392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-10
AI Technical Summary
Existing epoxy-based materials are unstable in color when exposed to heat, ultraviolet radiation, or chemicals, and are prone to yellowing or darkening. Furthermore, conventional materials are not stable enough during storage and distribution.
Compositions using non-aromatic epoxy resins, non-aromatic anhydride-based curing agents, colorants, and nitrogen-containing catalysts ensure that the catalyst is solid at temperatures below 25°C and is stable for at least one day at temperatures between 20°C and 25°C during storage, including curable compositions with long pot life.
It achieves color stability and strong adhesion under harsh conditions, with a pot life of at least one to twenty days. It is suitable for adhesives and coatings for electronic devices, and features color stability and strong adhesion.
Smart Images

Figure GDA0005183503950000031 
Figure GDA0005183503950000101 
Figure GDA0005183503950000111
Abstract
Description
Technical Field
[0001] Field of the Invention This invention relates to long-life, color-stable epoxide compositions and articles containing such compositions. Background Art
[0002] Epoxy-based materials have high adhesion and good durability for bonding to materials such as metals, glass, ceramics, and plastics. Conventional epoxy-based materials are not color stable and they visibly yellow or darken when exposed to heat, ultraviolet radiation, or chemicals. Summary of the invention
[0003] In one aspect, the present invention relates to a curable composition comprising a non-aromatic epoxy resin, a non-aromatic anhydride-based curing agent, a colorant, and a nitrogen-containing catalyst, wherein the nitrogen-containing catalyst is solid at a temperature below 25°C.
[0004] In another aspect, the present invention provides a method of using a curable composition. The method includes providing a curable composition comprising a non-aromatic epoxy resin, a non-aromatic anhydride-based curing agent, a colorant, and a nitrogen-containing catalyst, when the nitrogen-containing catalyst is solid at a temperature below 25°C. The method also includes storing the curable composition at a temperature between 20°C and 25°C for at least 1 day, dispensing the curable composition onto a substrate, and optionally curing the curable composition.
[0005] The above summary of this specification is not intended to describe each embodiment of the present invention. The details of one or more embodiments of the present invention are also listed in the following specific embodiments. Other features, objects and advantages of the present invention will be apparent from the specific embodiments and claims. DETAILED DESCRIPTION
[0006] As used herein, the terms "aliphatic" and "cycloaliphatic" refer to compounds having a hydrocarbon group that is an alkyl or alkylene group.
[0007] The term "alkyl" refers to a monovalent group that is an alkane radical, which is a saturated hydrocarbon. The alkyl group may be linear, branched, cyclic, or a combination thereof, and typically has 1 to 20 carbon atoms. In some embodiments, the alkyl group contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, and ethylhexyl.
[0008] The term "alkylene group" refers to a divalent group that is a radical of an alkane. An alkylene group may be linear, branched, cyclic, or a combination thereof. An alkylene group typically has 1 to 20 carbon atoms. In some embodiments, an alkylene group contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. The radical centers of an alkylene group may be on the same carbon atom (i.e., an alkylidene group) or on different carbon atoms.
[0009] As used herein, the term "aromatic" refers to a compound having a hydrocarbon group that is an aryl or arylene group.
[0010] As used herein, the term "non-aromatic" refers to compounds that do not include an aryl or arylene group.
[0011] The term "aryl" refers to a monovalent group that is aromatic and carbocyclic. The aryl group may have one to five rings connected or fused to the aromatic ring. Other ring structures may be aromatic, non-aromatic, or a combination thereof. Examples of aryl groups include, but are not limited to, phenyl, biphenyl, terphenyl, anthryl, naphthyl, acenaphthyl, anthraquinone, phenanthrenyl, anthracenyl, pyrenyl, perylenyl, and fluorenyl.
[0012] The term "arylene" refers to a divalent group that is carbocyclic and aromatic. The group has one to five rings that are connected, fused, or a combination thereof. The other rings may be aromatic, non-aromatic, or a combination thereof. In some embodiments, the arylene group has up to 5 rings, up to 4 rings, up to 3 rings, up to 2 rings, or one aromatic ring. For example, the arylene group may be a phenylene group.
[0013] In many applications, it may be desirable to obtain a one-part curable composition that does not require separate storage and components that are mixed when distributing or when approaching distribution. It may also be desirable that such one-part curable compositions be stable at room temperature over an extended period of time (e.g., without hardening or viscosity increase to a degree that is difficult or impossible to distribute): at least one day in some cases, at least seven days in some cases, at least ten days in some cases, or at least twenty days in some cases. Under comparable performance, stability over as long a period as possible is required in many applications. This stability can be represented by a pot life: a measure of the effective available / distributable life of the curable composition when stored at room temperature.
[0014] In some embodiments, the present invention relates to a curable composition comprising a non-aromatic epoxy resin, a non-aromatic anhydride-based curing agent, a colorant, and a nitrogen-containing catalyst, wherein the nitrogen-containing catalyst is solid at a temperature below 25°C. The curable composition may also include a series of optional additives. Generally, the curable composition has strong adhesion properties when cured and is color stable even when exposed to harsh conditions (e.g., chemical exposure, heat exposure, UV aging).
[0015] In some embodiments, the curable composition may include at least one non-aromatic epoxy resin. Suitable non-aromatic epoxy resins include epoxy resins based on diglycidyl ether and alicyclic epoxy resins such as diepoxy acetals, diepoxy adipates, diepoxy carboxylates, and epoxy resins based on dicyclopentadiene; isocyanurate derivative epoxy resins such as triglycidyl isocyanurate; and hydrogenated epoxy resins prepared by hydrogenating aromatic rings in aromatic epoxy resins, aromatic epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, aralkyl type epoxy resins, and biphenyl aralkyl type epoxy resins. Two or more of these resins can be used in combination.
[0016] In some embodiments, the non-aromatic epoxy resin may be a colorless or light-colored and / or transparent resin. In this manner, the color of the curable composition of the present description may be established by the colorant included in the composition.
[0017] In some embodiments, the non-aromatic epoxy resin is a liquid epoxy resin at room temperature. In some embodiments, the non-aromatic aromatic epoxy resin is the main reactive component of the curable composition. In some embodiments, the curable composition comprises 50 to 95 or 60 to 90 parts by weight of the non-aromatic epoxy resin per 100 parts of the total weight of the reactive components.
[0018] In some embodiments, the curable composition further comprises one or more anhydride-based curing agents. As used herein, "anhydride-based curing agent" refers to a compound formed by dehydrating a dicarboxylic acid according to formula (I), wherein A is an aliphatic or alicyclic linking group.
[0019]
[0020] Examples of suitable anhydride-based curing agents include linear polymeric anhydrides such as polysebacic anhydride and polyazelaic anhydride; cycloaliphatic anhydrides such as methyltetrahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride; simple cycloaliphatic anhydrides such as succinic anhydride, substituted succinic anhydride, citric anhydride, maleic anhydride, and maleic anhydride, dodecyl succinic anhydride, special adducts of maleic anhydride, or polycyclic alicyclic anhydrides. In some embodiments, a combination of two or more anhydride-based curing agents may be used; for example, a combination of tetrahydrophthalic anhydride and citric anhydride, a combination of methylhexahydrophthalic anhydride and dodecyl succinic anhydride, or a combination of methylnadic anhydride and maleic anhydride.
[0021] In some embodiments, the curable composition comprises 10 to 45, 10 to 30, or 12 to 25 parts by weight of an anhydride-based curing agent per 100 parts total weight of reactive components. In some embodiments, the curing agent consists of or consists essentially of an anhydride-based curing agent.
[0022] In some embodiments, the curing agent may optionally include one or more amine-based curing agents. In some embodiments, the amine-based curing agent may be non-aromatic. Examples of suitable amine-based curing agents include: liquid polyetheramines such as JEFFAMINE T-403 and JEFFAMINED-230, commercially available from Huntsman Corp.; 4,7,10-trioxatridecane-1,13-diamine and 4,9-dioxatridecane-1,12-diamine; polyamidoamines such as VERSAMID 125 and GENAMID 490, commercially available from BASF; ethyleneamines such as DETA (diethylenetriamine), TETA (triethylenetetramine), TEPA (tetraethylenepentamine), and AEP (N-aminoethylpiperazine); alicyclics such as PACM (bis-(p-aminocyclohexyl)methane), DACH (diaminocyclohexane), and DMCH (bis-(dimethyldiaminocyclohexyl)methane); isophoronediamine and norbornenedimethylamine.
[0023] In some embodiments, the curing agent may include a colorless or light-colored and / or transparent curing agent. In this way, the color of the curable composition of the present specification can be established by adding one or more colorants to the composition.
[0024] In some embodiments, the curing agent is a liquid at room temperature.
[0025] In some embodiments, the curable composition includes 10 to 35 parts by weight, 10 to 20 parts by weight, or 12 to 18 parts by weight of an amine-based curing agent per 100 parts total weight of reactive components.
[0026] In some embodiments, the curable composition of this specification may include one or more colorants (or dyes or pigments). As used herein, the term "colorant" refers to a substance added to the composition to give the composition color and / or other opacity-the term "colorant" does not cover reactive components or any other materials added to the curable composition to achieve solidification. For example, one or more colorants may be present in the curable composition so that the cured curable composition "color matches" the color of the adjacent parts (for example, the external / user-visible parts of the electronic device) of the cured composition. Various types of colorants may be applicable to curable compositions, including commercially available dyes for azo (for example, Oil Red O) and anthraquinone (for example, Solvent Blue 35) family colorants. In some embodiments, suitable colorants may include organic dyes, such as azo, anthraquinone, phthalocyanine blue and phthalocyanine green, quinacridone, dioxazine, isoindolinone or vat dyes. In some embodiments, the colorant comprises copper phthalocyanine (blue and green), azo, diarylide, quidacridone, isoindoline, diketopyrrole, indanthrone, carbon black, iron oxide, or titanium dioxide.
[0027] In some embodiments, the colorant may be dispersed or otherwise disposed in the curable composition (and the cured composition) such that the composition has a uniform or substantially uniform color throughout the composition over a wide range of operating temperatures (e.g., between -40 degrees Celsius and 85 degrees Celsius). In some embodiments, the colorant may be stable in the curable composition (i.e., (i) does not react or does not substantially react with or is not consumed by the components of the curable composition; and (ii) remains uniformly or substantially uniformly dispersed or otherwise disposed in the working fluid over an extended period of time over a wide range of operating temperatures).
[0028] In some embodiments, the colorant may be present in the curable composition in an amount between 0.1 wt % and 10 wt % or between 0.1 wt % and 5 wt % based on the total weight of the reactive components.
[0029] The curable composition may include additional optional additives. These optional additives may be solid or liquid and may be reactive or non-reactive. Fillers are suitable additives including thermally conductive fillers, flame retardants (such as ATH (aluminum trihydrate) or phosphate flame retardants), nanoparticles or functionalized nanoparticles, chain extenders, toughening agents or combinations thereof. These components are typically solid, but some additive components may be liquid, and these liquid components may be suitable.
[0030] Examples of non-reactive additives include fillers, flame retardants, nanoparticles, and tougheners. Particularly suitable non-reactive additives are fillers such as metal oxides (silicon dioxide, titanium dioxide, magnesium oxide, etc.) and thermal conductivity enhancers such as boron nitride. In some embodiments, the curable composition can be highly filled; for example, 50% by weight of the curable composition can be a filler (such as silicon dioxide or titanium dioxide). In some embodiments, these fillers can be selected according to their geometric structure and rheological properties. In some embodiments, these fillers can have a substantially spherical shape. In some embodiments, the size and distribution of these fillers can be selected according to the best or desired flow characteristics. In some embodiments, the filler can have a bimodal size distribution. In some embodiments, the filler includes at least two particle size groups: one is greater than 3 microns, and one is less than 3 microns.
[0031] In some embodiments, the additives for the curable composition of the present specification may include one or more epoxy resin tougheners. Such tougheners can be used, for example, to improve some properties of the composition so that they do not break brittlely when broken. Examples of available tougheners (also referred to as elastomer modifiers) include polymer compounds having both a rubber phase and a thermoplastic phase, such as: a graft copolymer having a polymerized diene rubber core and a polyacrylate or polymethacrylate shell; a graft copolymer having a rubber core and a polyacrylate or polymethacrylate shell; elastomer particles polymerized in situ by free radical polymerizable monomers and copolymer stabilizers in epoxides; elastomer molecules, such as polyurethanes and thermoplastic elastomers; separated elastomer precursor molecules; combined molecules comprising epoxy resin segments and elastomer segments; and mixtures of such separated molecules and combined molecules. These combined molecules can be prepared by reacting epoxy resin materials with elastomer segments; the reaction leaves reactive functional groups, such as unreacted epoxy groups, on the reaction product. The use of toughening agents in epoxy resins is described in Advances in Chemistry Series, Rubbery-Modified Thermoset Resins, edited by CK Riew and JK Gillham, No. 208, American Chemical Society, Washington, 1984. The amount of toughening agent to be used depends in part on the ultimate physical characteristics desired for the cured resin.
[0032] In some embodiments, the toughening agent in the curable composition of the present specification may include a graft copolymer having a polymerized diene rubber backbone or core onto which is grafted a shell comprising an acrylate or methacrylate, a monovinyl aromatic hydrocarbon, or a mixture of these substances, such as those disclosed in U.S. Pat. No. 3,496,250 (Czerwinski). The rubber backbone may comprise polymerized butadiene, or a polymerized mixture of butadiene and styrene. The shell comprising polymerized methacrylate may be a lower alkyl methacrylate (C 1-4 The monovinyl aromatic hydrocarbon may be styrene, α-methylstyrene, vinyltoluene, vinylxylene, ethylvinylbenzene, isopropylstyrene, chlorostyrene, dichlorostyrene and ethylchlorostyrene.
[0033] Another example of a useful toughening agent is an acrylate core-shell graft copolymer in which the core or backbone is a glass transition temperature (T g ) polyacrylate polymers below about 0°C, such as those grafted with T gA polymethacrylate polymer shell such as poly(butyl acrylate) or poly(isooctyl acrylate) of poly(methyl methacrylate) at about 25°C. For acrylic core / shell materials, the "core" will be understood to be T g Acrylic polymer <0°C, and "shell" will be understood as T g Acrylic polymers at >25° C. Some core / shell toughening agents (e.g., including acrylic core / shell materials and methacrylate-butadiene-styrene (MBS) copolymers, where the core is a crosslinked styrene / butadiene rubber and the shell is a polymethacrylate) are commercially available, for example, from The Dow Chemical Company under the trade name “PARALOID”.
[0034] Another useful core-shell rubber is described in U.S. Patent Application Publication 2007 / 0027233 (Yamaguchi et al.). The core-shell rubber particles as described in the document include a crosslinked rubber core (in most cases a crosslinked copolymer of butadiene), and a shell, which is preferably a copolymer of styrene, methyl methacrylate, glycidyl methacrylate, and optionally acrylonitrile. Specific examples are Kane Ace M731, M732, M511, MX-553, and M300, which are commercially available from Kaneka.
[0035] In some embodiments, the toughening agent may include acrylic core / shell polymers; styrene-butadiene / methacrylate core / shell polymers; polyether polymers; carboxyl-terminated or amino-terminated acrylonitrile / butadiene; carboxylated butadiene, polyurethane, or combinations thereof.
[0036] In some embodiments, the toughening agent may be present in the curable composition in an amount between 0.1 wt % and 10 wt %, between 0.1 wt % and 5 wt %, between 0.5 wt % and 5 wt %, between 1 wt % and 5 wt %, or between 1 wt % and 3 wt %, based on the total weight of the curable composition.
[0037] In some embodiments, the curable composition includes a catalyst. In some embodiments, the catalyst is a nitrogen-containing catalyst. In some embodiments, the nitrogen-containing catalyst is solid at room temperature or at a temperature below 25 ° C. In some embodiments, a solid nitrogen-containing catalyst can make the single-component packaging of the curable composition have a surprisingly long shelf life. Since the nitrogen-containing catalyst remains solid at room temperature, the shelf life of such a curable composition is significantly long as the curable composition remains at room temperature. Suitable solid nitrogen-containing catalysts include FUJICURE FXR-1081 (obtained from T&K Toka Corporation, Saitama, Japan), Ancamine 2441 (obtained from Evonik Industries AG, Essen, Germany) and Ancamine 2442 (obtained from Evonik Industries AG, Essen, Germany). For many applications, doubling the viscosity from an initial value or reference value can be a reasonable definition of the shelf life. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 1 day. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 3 days. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 7 days. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 10 days. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 14 days. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 20 days. In some embodiments, the viscosity of the curable composition does not increase to more than 200% of the initial viscosity after 21 days.
[0038] In some embodiments, once cured, the curable composition of the present specification may exhibit thermal, mechanical and rheological properties, which makes the composition particularly useful as an adhesive or coating for decorative applications, which requires strong adhesion to the substrate over time and strong adhesion to the substrate once a sudden impact (i.e., strong dripping performance). In some embodiments, in addition to having strong adhesion, durability, dripping performance, the curable composition of the present specification may exhibit color stability in the presence of heat, UV light and household chemicals and when exposed to chemical anodizing or dye injection processes. In this regard, in some embodiments, once the anodizing bath simulation process described in the embodiments of the present invention is exposed to an acid bath, the cured composition of the present invention may exhibit a ΔE 94 color change of less than 1, less than 0.8, or less than 0.5. In some embodiments, when exposed to ultraviolet light according to the UV exposure test described in the embodiments of the present invention, the cured composition of the present invention may exhibit a ΔE 94 color change of less than 5, less than 3, less than 2, or less than 1.
[0039] In some embodiments, the cured composition shows the necessary performance properties for the adhesive suitable for electronic devices. In this regard, in some embodiments, the cured composition can have an overlap shear value of at least 25MPa, at least 30MPa or at least 35MPa on an etched aluminum substrate. For the purpose of this specification, the overlap shear value is measured according to ASTM D-1002-72. In addition, the cured composition can have a cantilever notch toughness value of at least 20J / m, at least 30J / m or at least 40J / m. For the purpose of this specification, the cantilever notch toughness value is measured according to ASTM D-256.
[0040] In some embodiments, the cured composition may have a tensile elongation of at least 10% and a glass transition temperature of at least 80 degrees Celsius.
[0041] Also disclosed herein are articles made from the above-described curable compositions.
[0042] In some embodiments, the product of this specification can be manufactured by forming the curable composition (before, after or during curing) into a desired or predetermined shape. The shaping of the curable composition (or curing composition) can be carried out using machining, micromachining, microreplication, molding, extrusion injection molding, ceramic pressing, etc. In this way, the curable composition of this specification can be used to form a product of any size or shape. For example, in some embodiments, the product of this specification may include a user-visible or decorative component of an electronic device (for example, a housing or shell for a mobile phone, a tablet computer, a watch, a headset or a laptop).
[0043] In other embodiments, the curable composition can be applied to a substrate and cured. The article can include a substrate comprising a first major surface and a second major surface, and a coating located on at least a portion of the second major surface of the substrate, wherein the coating comprises a cured layer of the curable composition.
[0044] The coating can be applied on a wide range of substrates. Examples of suitable substrates include metal substrates, ceramic substrates, glass substrates, or polymer substrates. The substrate can be in a variety of shapes, such as a plate or a tube, and can have a smooth or irregular surface, and can be hollow or solid.
[0045] The curable composition can be applied to the substrate to form a curable layer using a variety of techniques including dip coating, forward and reverse roll coating, wire wound rod coating, and die coating. Die coaters include knife coaters, slot coaters, slide coaters, hydraulic bearing coaters, slide curtain coaters, and drop die curtain coaters. Once applied, the curable composition is allowed to cure to form a cured coating.
[0046] The coating thickness varies according to the desired use of the coating. In some embodiments, the coating thickness can be in the range of 25 microns (1 mil) to 1 millimeter. The curable composition can be applied to the substrate in an available thickness in the range of 5 microns to 10000 microns, 25 microns to 10000 microns, 100 microns to 5000 microns, or 250 microns to 1000 microns.
[0047] In some embodiments, the curable composition can be used as a structural adhesive, that is, the curable composition can bond the first substrate to the second substrate after curing. In some embodiments, this specification provides a kind of product, the product includes a first substrate, a second substrate and a cured composition, the cured composition is arranged between the first substrate and the second substrate and adheres the first substrate to the second substrate, wherein the cured composition is a reaction product of any one of the curable compositions of the curable compositions of this specification. In some embodiments, the first substrate and / or the second substrate can be at least one of a metal, a ceramic and a polymer.
[0048] The curable composition can be coated on the substrate with an available thickness in the range of 5 microns to 10000 microns, 25 microns to 10000 microns, 100 microns to 5000 microns or 250 microns to 1000 microns. Available substrates can have any properties and composition, and can be inorganic or organic. Representative examples of available substrates include ceramics, siliceous substrates including glass, metals (for example, aluminum or steel), natural stone and artificial stone, woven and nonwoven products, polymer materials including thermoplastic and thermosetting polymer materials (such as poly (methyl) acrylate, polycarbonate, polystyrene, styrene copolymers such as styrene acrylonitrile copolymers, polyesters, polyethylene terephthalate), siloxanes, paints (such as those based on acrylic resins), powder coatings (such as polyurethane or mixed powder coatings) and wood; and the composites of the above-mentioned materials.
[0049] In some embodiments, the curable composition of the present specification can be used as a decorative inlay for an electronic device or a component of an electronic device. Typically, a decorative inlay refers to a component that is positioned in a gap or hole in another material and is positioned, sized, and shaped so that it fills (or substantially fills) the gap or hole and is flush (or substantially flush) with the material adjacent to the component / inlay. In some embodiments, the curable composition can be used as a decorative inlay for a housing or shell or an electronic device (a mobile phone, a tablet computer, or a laptop computer). The housing or shell can be formed of a metal (e.g., aluminum).
[0050] Also disclosed herein is a method of dispensing a curable composition. In some embodiments, the method of dispensing a curable composition may include providing a curable composition comprising a non-aromatic epoxy resin, a non-aromatic anhydride-based curing agent, a colorant, and a nitrogen-containing catalyst, wherein the nitrogen-containing catalyst is solid at a temperature below 25°C. The method may also include storing the curable composition at 20°C to 25°C for at least 1 day, at least 7 days, at least 10 days, at least 14 days, at least 20 days, or at least 21 days, then dispensing the curable composition on a substrate, and then optionally curing the curable composition.
[0051] Example
[0052] Table 1: Materials
[0053]
[0054]
[0055] Test Method
[0056] Definition of applicable period and test method
[0057] Viscosity measurements were used to determine the pot life of the uncured composition. According to ASTM D3795-20, the viscosity of the curable epoxy resin was measured by shear rate scanning in cone and plate operation mode using a Discovery HR-3 rheometer (available from TA Instruments, New Castle, DE, New Castle, Delaware). The 40 mm (mm) diameter stainless steel cone and 60 mm plate with a cone angle of 0.03499 radians were used at 25 ° C (77 ° F) for measurement. Two to three grams of curable resin composition were placed between the cone and the plate. The cone and the plate were then closed to provide a 0.051 mm gap (at the top) filled with resin. Excess resin was scraped off from the edge with a spatula. The viscosity was measured using a shear rate scan of 0.01 Hz to 100 Hz, and the viscosity change over time at 10 Hz was monitored. Between measurements, the samples were stored at 23 ° C to 25 ° C (73 ° F to 79 ° F). If the viscosity reaches a value twice the initial value measured, the test is stopped. This time is designated as the pot life of the composition.
[0058] UV exposure test
[0059] UV exposure testing was performed according to ASTM D4459-21. A cured epoxy resin panel measuring 6.35 cm x 6.35 cm (2.5 in x 2.5 in) and 1.6 mm thick was exposed to 2.4 W / m at 420 nm at 35°C and 30% relative humidity. 2 The samples were continuously exposed to a 4500-watt xenon lamp for up to 240 hours.
[0060] Color Change Test Method
[0061] The color change of the patches was measured as follows: The initial color of each patch was measured using a Konica CM3700A spectrophotometer (available from Konica Minolta Sensing Americas, Inc. Ramsey, New Jersey) to include the specular component (SCI) mode with a 10 degree observation angle. After the patches were exposed to the anodizing bath simulation process, the color was measured again. The color difference before and after the acid bath exposure was calculated using the ΔE 94 calculation as specified by the International Commission on Illumination (CIE), where the l:C ratio was 2:1 under illuminant F02 (cool white fluorescent). A ΔE 94 color change of less than 1 is generally considered to be imperceptible to the human eye.
[0062] Preparation of acid bath for simulating anodizing process
[0063] A suitable anodizing process for electronic devices made of aluminum is described in U.S. Patent Publication No. 2013 / 0270120A1. The process steps that have the greatest impact on the color of the adhesive are desmutting and chemical polishing. The desmutting bath is prepared using 30% nitric acid. The chemical polishing bath is prepared using 85% phosphoric acid.
[0064] Anodizing bath simulation process
[0065] The example and comparative example patches were each immersed in a decontamination bath at 25°C for 180 seconds; immediately thereafter rinsed in deionized water for 30 seconds. Next, the patches were immersed in a chemical polishing bath preheated to 80°C for 180 seconds. They were then rinsed in deionized water for 60 seconds. The patches were then allowed to dry under ambient conditions before final color measurements were taken.
[0066] Overlap Shear (OLS) Test
[0067] OLS values are measured according to ASTM D-1002-72. The sample adhesive composition is directly applied to an untreated 2.5cm×10cm×0.3cm (1 inch×4 inches×0.125 inches) test panel, and the untreated second test panel is immediately placed against the sample adhesive composition on the first test panel so that the overlapping area is 1.3cm×2.5cm (0.5 inches×1 inches). The fixture is applied to the overlapping area. The test panel is aluminum. A small amount of sample adhesive composition squeezes the overlapping area and allows to stay. Bonding is cured at 120°C for 1 hour. The fixture is then removed, and the overlapping bonding is sheared (OLS) with a crosshead speed of 0.25cm / minute (0.1 inches / minute) on a tensile tester. The overlapping shear value is recorded in pounds per square inch and converted into megapascals (MPa). The overlapping shear value represents the average value of three repetitions.
[0068] Tensile modulus test
[0069] Tensile modulus was measured according to ASTM D638-14 on three sample adhesive compositions taken from molded Type IV dogbones having a thickness of about 3.0 mm.
[0070] Elongation at break test
[0071] The percent elongation at break values were measured according to ASTM D638-14 at a crystal pulling rate of 5 mm / min.
[0072] Glass transition temperature Tg
[0073] Tg values are measured by differential scanning calorimetry (DSC) according to ASTM E1356-08 at a scan rate of 10°C / min.
[0074] Sample Preparation EX1-3 (General Mixing Procedure for Preparing Curable Compositions)
[0075] The compositions summarized in Table 2, YX8000D, L52D, DDSA were used. E58005, MA17, and TiO2 were weighed into plastic cups, the size of each plastic cup varied with the amount of material added. The materials were mixed at room temperature in a DAC 600FVZ SPEEDMIXER (FlackTek Incorporated, Landrum, SC) at 1800 rpm for six minutes. H21 was then added to the mixture and mixed at 2000 rpm for 3 minutes at room temperature. The mixture was cooled to room temperature before adding F-1081. F-1081 was then added and mixed at about 1800 rpm for 2 minutes and subsequently degassed at 800 rpm for 3 minutes under 30 Torr vacuum using a DAC 600.2 VAC-P SPEEDMIXER (FlackTek Incorporated, Landrum, SC) to prepare an adhesive component.
[0076] Examples of color stable epoxy adhesive compositions are listed in Table 2.
[0077] Table 2. Adhesive compositions of Comparative Example (CE) CE1 and Examples (EX) EX1-3.
[0078] All amounts in Table 2 are in wt% by mass .
[0079] YX8000D L52D DDSA M-731 E58005 MA17 F2098 F-1081 TiO2 H21 I-1035 EX1 25 17.5 21 - 23 - - 4.5 6 3 - EX2 25 19 14 - 23 5.5 - 4.5 6 3 - EX3 25 17.5 20 - 23 - - 4.5 6 3 1 CE1 40.5 17.5 15.5 17 - - 0.5 - 6 3 -
[0080] The viscosities of the freshly prepared epoxy resins and their pot lives are summarized in Table 3. The viscosity of the freshly prepared epoxy resins refers to the viscosity measured within 5 minutes after mixing of all compositions.
[0081] Table 3. Viscosity test results
[0082]
[0083] The elongation at break, tensile modulus, OLS, and Tg properties of the color stable epoxy resins are summarized in Table 4.
[0084] Table 4. Adhesive properties
[0085] Elongation at break (%) Tensile modulus(GPa) OLS(MPa) Tg(℃) EX1 14.2 2.23 26.8 73 EX2 18.0 1.97 24.9 72 EX3 12.5 2.00 26.6 76 CE1 4.7 1.75 20.9 97
[0086] The color measurement results are identified in Table 5.
[0087] Table 5. ΔE 94 color change after anodizing
[0088] ΔE after anodizing 94 ΔE 94 after 240 hours of UV exposure EX1 0.24 3.82 EX2 0.45 3.60 EX3 0.16 2.26 CE1 0.10 1.68
[0089] Sample Preparation EX4
[0090] YX8000D, L52D and DDSA are weighed into a DAC Speedmixer cup. Then use DAC Speedmixer to mix YX8000D, L52D and DDSA for 2 minutes at approximately 2000rpm. Then add SFP-130MC and mix for 6 minutes at approximately 2000rpm. Then add FB-5SDC and mix for 6 minutes at approximately 2000rpm. Before adding F-1081, the mixture is cooled to room temperature. Then add F-1081 and mix for 2 minutes at approximately 1800rpm. Then use vacuum DAC Speedmixer to degas the resulting mixture for 5 minutes at approximately 800rpm under 3 torr vacuum.
[0091] Table 6. Binder composition of EX4. All amounts in Table 6 are in wt% by mass.
[0092] YX8000D FB-5SDC SFP-130MC L52D DDSA F-1081 EX4 11.94 59.70 14.93 7.96 3.98 1.49
[0093] Viscosity was determined according to ASTM D3795-20. Glass transition temperature (Tg) was measured according to ASTM E1356-08. CTE was determined according to ASTM E831. All CTE samples were cured at 130°C for 1 hour. The test results are summarized in Table 7.
[0094] Table 7. Properties of adhesive compositions
[0095] Viscosity (25°C, at 10 / s shear rate) (Pa.s) Tg(℃) CTEα1(ppm / ℃) EX4 44.06 91 18.3
[0096] Various modifications and alterations of this invention will become apparent to those skilled in the art without departing from the scope and spirit of this invention.
Claims
1. A curable composition, comprising: Non-aromatic epoxy resins; Non-aromatic anhydride-based curing agents; Colorants; and A nitrogen-containing catalyst, wherein the nitrogen-containing catalyst is solid at a temperature below 25°C.
2. The curable composition of claim 1, wherein the curable composition comprises 10 to 45 parts by weight of anhydride-based curing agent per 100 parts by total weight of reactive components.
3. The curable composition of claim 1, wherein the non-aromatic anhydride-based curing agent comprises an aliphatic or alicyclic moiety.
4. The curable composition of claim 1, wherein the curable composition comprises 50 to 95 parts by weight of the non-aromatic epoxy resin per 100 parts by total weight of reactive components.
5. The curable composition of claim 1, wherein the colorant is present in the curable composition in an amount between 0.1 wt% and 10 wt% based on the total weight of the reactive components.
6. The curable composition of claim 1, wherein the curable composition has an initial viscosity, and after exposure to 25°C for 1 day, the measured viscosity of the curable composition is less than 200% of the initial viscosity.
7. The curable composition of claim 1, wherein the curable composition has an initial viscosity, and after exposure to 25°C for 3 days, the measured viscosity of the curable composition is less than 200% of the initial viscosity.
8. The curable composition of claim 1, wherein the curable composition has an initial viscosity, and after exposure to 25°C for 7 days, the measured viscosity of the curable composition is less than 200% of the initial viscosity.
9. The curable composition of claim 1, wherein the curable composition has an initial viscosity, and after exposure to 25°C for 10 days, the measured viscosity of the curable composition is less than 200% of the initial viscosity.
10. The curable composition of claim 1, wherein the curable composition has an initial viscosity, and after exposure to 25°C for 20 days, the measured viscosity of the curable composition is less than 200% of the initial viscosity.
11. The curable composition of claim 1, wherein the curable composition is dispensable after 7 days at 25°C.
12. The curable composition of claim 1, wherein the curable composition further comprises an epoxy-terminated elastomer.
13. The curable composition of claim 1, wherein the curable composition has a Tg of at least 60°C.
14. The curable composition of claim 1, further comprising between 1 and 10 parts by weight of maleated rubber per 100 parts by total weight of reactive components.
15. The curable composition of claim 1, wherein the curable composition exhibits anodization color stability, wherein exhibiting anodization color stability means that the curable composition, once cured, has a ΔE94 color change of 0.5 or less after anodization.
16. The curable composition of claim 1, wherein the curable composition exhibits UV color stability, wherein exhibiting UV color stability means that the curable composition, once cured, has a ΔE94 color change of 4.0 or less after 240 hours of UV exposure.
17. The curable composition of claim 1, wherein the curable composition permanently adheres to aluminum.
18. The curable composition of claim 1, wherein the curable composition exhibits an elongation at break of at least 10%.
19. The curable composition of claim 1, wherein the curable composition comprises at least 50 wt% silica filler.
20. The curable composition of claim 19, wherein the silica filler comprises spherical particles.
21. The curable composition of claim 20, wherein the silica filler has a bimodal size distribution.
22. The curable composition of claim 1, wherein the curable composition comprises at least two different non-aromatic anhydride-based curing agents.
23. An article comprising a cured composition, wherein the cured composition is a reaction product of the curable composition of claim 1.
24. A method of using a curable composition, the method comprising: Providing a curable composition comprising a non-aromatic epoxy resin, a non-aromatic anhydride-based curing agent, a colorant, and a nitrogen-containing catalyst, wherein the nitrogen-containing catalyst is solid at a temperature below 25°C; storing the curable composition at a temperature between 20°C and 25°C for at least 1 day; dispensing the curable composition onto a substrate; as well as The curable composition is optionally cured.
25. The method of claim 24, wherein the curable composition is stored at a temperature between 20°C and 25°C for at least 7 days.
Citation Information
Patent Citations
Process for producing modified epoxy resin
US20070027233A1
Cosmetic defect reduction in anodized parts
US20130270120A1
Blends of epoxy resins and acrylonitrile butadiene-styrene graft copolymers
US3496250A